Designing a Sciences Learning Media Based on Website and Integrated with Youtube Videos - Swandi, Ahmad; Rahmadhanningsih, Sri; Arsyad, Muhammad; Jamaluddin, Asham Bin; Safira, Ifa; Pratiwi, Andi Citra (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2022)
There are three types of learning styles, to meet the learning styles of students, both visual and auditory types, there needs to be an innovation of supportive and appropriate learning media. In addition, the learning media can also be one of the supporting media in the implementation of online learning. Therefore, a research was conducted that aims to produce online-based learning media that is integrated with video and audio. The research method used is Research and Development (R&D) with a 3D model consisting of 3 stages, namely Definition, Design. The products that have been produced are then validated by 3 experts to determine eligibility based on expert assessments. Then a limited trial was conducted on 6 students to find out their response to the learning website and become one of the references in improving the media. The expert's assessment shows that the Website-Based Sciences Learning Media product that is integrated with video and audio is very feasible, which is marked by a percentage score of 91,68%. In addition, students' perceptions of the use of Website-Based Sciences Learning Media that are integrated with video and audio are at a value of 91,31% with a good category.